2022
DOI: 10.3390/coatings12030314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Anodizing Temperature on Microstructure and Tribological Properties of 6061 Aluminum Alloy Anodic Oxide Films

Abstract: Anodizing a simple and effective method to improve the wear resistance of 6061 aluminum alloy. In this study, the microstructure of 6061 aluminum alloy oxide films (AAO) was adjusted by changing the electrolyte temperature (5, 15, and 25 °C) using 160 g/L sulfuric acid as the electrolyte. The phase composition, microstructure, and morphological characteristics of the specimens were detected using X-ray diffractometer and field emission scanning electron microscopy (SEM). The hardness, elastic modulus, and trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…[ 20,33 ] The generally higher hardness of the hard anodic coatings is a result of their denser pore structure, when compared to the anodized specimens. [ 34 ] Kwolek et al [ 35 ] also observed a decrease in hardness with an increase in the thickness of a hardanodic coating, but they give no further explanation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20,33 ] The generally higher hardness of the hard anodic coatings is a result of their denser pore structure, when compared to the anodized specimens. [ 34 ] Kwolek et al [ 35 ] also observed a decrease in hardness with an increase in the thickness of a hardanodic coating, but they give no further explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Etching processes in aluminum were previously described for different acid solvents; however, obtaining nanoporous structures remains a challenge, since most large micropores were obtained using hydrochloric acid (HCl) [ 21 , 22 ], or even using oxalic acid/phosphoric acid mixtures (C 2 H 2 O 4 /H 3 PO 4 ) [ 23 ]. On the other hand, nanopores were obtained using an anodizing process involving sulfuric acid (H 2 SO 4 ) dipping [ 24 ]; however, the small dimensions of the pores prevented the further deposition of nanoparticles. In our case, when we used HNO 3 (35% during 35 min) as the etching chemical to obtain nanopores via a simple dipping process, a homogeneous structure with pore sizes of ~ 30 nm was formed enabling the deposition of mPEG-b-PLA micelles.…”
Section: Discussionmentioning
confidence: 99%
“…Tsyntsaru et al 7 reported these precipitates are caused by the alloying elements, such as Si in the aluminum foil. The oxygen bubbles can form and burst during the electrochemical process at the oxide/electrolyte interface as explained by Feng et al 24 The presence of these defects is not significant for the suggested target applications.…”
Section: Ecs Advances 2023 2 042501mentioning
confidence: 99%